2018
DOI: 10.1136/bjophthalmol-2018-311846
|View full text |Cite
|
Sign up to set email alerts
|

Resting nailfold capillary blood flow in primary open-angle glaucoma

Abstract: Reduced resting nailfold capillary blood flow is present in POAG independent of covariates such as blood pressure, pulse and IOP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 23 publications
(17 reference statements)
1
19
0
1
Order By: Relevance
“…This degeneration may cause the aforementioned alterations in the peripheral vessels, including elastosis, oxidative stress, and vascular endothelial dysfunction, leading to vascular stiffness [9]. Similar results related to lower peripheral blood flow in patients with HFG and NC were reported by Cousins et al [49], who explored resting peripheral blood flow at the nailfold in patients with POAG (HTG and NTG), which was found to be significantly lower compared with that in normal controls.…”
Section: Discussionsupporting
confidence: 52%
“…This degeneration may cause the aforementioned alterations in the peripheral vessels, including elastosis, oxidative stress, and vascular endothelial dysfunction, leading to vascular stiffness [9]. Similar results related to lower peripheral blood flow in patients with HFG and NC were reported by Cousins et al [49], who explored resting peripheral blood flow at the nailfold in patients with POAG (HTG and NTG), which was found to be significantly lower compared with that in normal controls.…”
Section: Discussionsupporting
confidence: 52%
“…We customized a high throughput PCR-based strategy to identify differentially expressed miRNAs relevant to glaucoma, then applied this tool to test AqH and plasma from glaucoma patients and cataract controls. We focused our analysis on plasma samples; in addition to its ease of collection (relative to AqH, which requires an elective procedure), at least some glaucoma endophenotypes are associated with vascular dysfunction,19,20 supporting the potential relevance for plasma biomarkers as a diagnostic tool for glaucoma 2123. Moreover, our complete dataset included matched AqH samples for each subject, allowing comparisons between the two sample types and further investigation of ocular miRNAs in glaucoma etiology.…”
mentioning
confidence: 99%
“…37 However, the minimal decrease is in contrast with another study that found significantly decreased blood flow in both patients with HTG and NTG compared with controls. 36 This difference may be the result of a higher percentage of white participants compared with controls (72% in our study vs 91.5% in the prior study 41 ), different methods (using blood flow only in the fourth digit in our study vs using both the fourth and fifth digits in the previous study), and subjectivity in NFC blood flow analysis between the 2 investigations. A recent study found that patients with NTG showed more signs of vascular dysfunction compared with those with HTG, further demonstrating the possible differences in the pathophysiologic mechanisms between the 2 variants.…”
Section: Discussionmentioning
confidence: 54%
“…Lower mean (SD) nailfold capillary blood flow in patients with NTG compared with controls (40.1 [16.6] vs 70.9 [52.4] pL/s; P = .02) in our study is consistent with that of previous studies. 36,37 Systemic and IOP-independent vascular involvement in NTG may be noted in the context of Flammer syndrome, a primary vascular dysregulation entity with multiple manifestations that play a part in the pathogenesis of NTG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation